The Effectiveness of Plant Growth Promoting Rhizobacteria (PGPR) on the Growth of Root Nodules of Peanut Genotypes under Water Deficit Condition - Restiyah, Demy Afiya; Kisman, Kisman; Hemon, A Farid (Pascasarjana, Mataram University, 2024)
The deficiency of water sources and soil fertility are obstacles to producing peanuts in dry land. One of effort to increase production on dry land is the utilization of PGPR biofertilizers. This study aimed to determine the growth of plants and root nodules of several peanut genotypes applied with PGPR, to understand the interaction between several peanut genotypes and PGPR on plant growth and root nodules, and to examine the relationship between water deficit conditions and the formation of root nodules. This experiment used a Complete Randomized Design-split split-plot design with the main plots being D0 = optimal conditions (no water deficit) and D1 = water deficit. The subplots were P0 = no PGPR and P1 = with PGPR. The sub-subplots consisted of five peanut genotypes: V1 = Hypoma-I, V2 = Domba, V3 = Talam, V4 = Bison, and V5 = G300-II. The observations showed that the addition of PGPR resulted in higher plant growth compared to those without PGPR and had more effective root nodules in nitrogen fixation compared to treatments without PGPR. The application of PGPR and genotype did not show significant interaction on plant growth and root nodules under water deficit conditions. Water deficit significantly affected all parameters of plant growth and root nodules. PGPR significantly affected the parameters of leaf number rate, nodule number, and nodule weight. Genotype significantly affected the plant height rate. The interaction of water deficit and genotype significantly affected the leaf number rate, while the interaction of water deficit and PGPR, and the interaction of PGPR and genotype did not significantly affect all observation parameters.